2022
DOI: 10.1021/acs.inorgchem.2c02605
|View full text |Cite
|
Sign up to set email alerts
|

Cr–Ti Mixed Oxide Molecular Cages: Synthesis, Structure, Photoresponse, and Photocatalytic Properties

Abstract: The solvothermal reaction of titanium isopropoxide and chromate in the presence of benzoate produced two novel host−guest clusters encapsulating Cs + or H 3 O + , (H 3 O)@Ti 7 Cr 14 and Cs@Ti 7 Cr 14 . The most remarkable feature is that the Ti 7 O 7 ring is concentrically embraced by a Cr 14 O 14 ring to form a rigid Ti 7 Cr 14 host. ESI-MS and 133 Cs NMR revealed that the overall framework structures are preserved, whereas the benzoate ligands on the two clusters may be labile in solutions. Both (H 3 O)@ Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 68 publications
(119 reference statements)
1
5
0
Order By: Relevance
“…The positive slopes are consistent with n-type semiconductors . Since the conduction band bottom of many n-type semiconductors is 0.1 V below E fb , the pseudo conduction band (pCB) potential of Ti 10 Cd 2 is −0.42 V vs NHE. Meanwhile, the pseudo valence band (pVB) potential of Ti 10 Cd 2 is +1.96 V vs NHE.…”
Section: Resultssupporting
confidence: 55%
“…The positive slopes are consistent with n-type semiconductors . Since the conduction band bottom of many n-type semiconductors is 0.1 V below E fb , the pseudo conduction band (pCB) potential of Ti 10 Cd 2 is −0.42 V vs NHE. Meanwhile, the pseudo valence band (pVB) potential of Ti 10 Cd 2 is +1.96 V vs NHE.…”
Section: Resultssupporting
confidence: 55%
“…Moreover, from the electrochemical impedance spectra (EIS, Figure 7c), it can be observed that the hybrid Mn 2 Cd 4 /Ir(Cltpy) 2 system exhibits a smaller arc radius compared to the Mn 2 Cd 4 cluster, indicating lower charge transfer resistance and higher photoelectron transfer efficiency for the hybrid Mn 2 Cd 4 /Ir(Cltpy) 2 system. 2 Further evidence supporting the higher catalytic activity of the hybrid Mn 2 Cd 4 / Ir(Cltpy) 2 system is provided by photoluminescence measurements carried out at an excitation wavelength of 521 nm (Figure 7d). As seen in Figure 7d, the hybrid Mn 2 Cd 4 / Ir(Cltpy) 2 system exhibits an emission band close to 527 nm, which is significantly less intense than that of Ir(Cltpy) 2 , suggesting that the hybrid Mn 2 Cd 4 /Ir(Cltpy) 2 system has a greater charge separation efficiency.…”
Section: ■ Introductionmentioning
confidence: 72%
“…Carbon dioxide is widely recognized as the main greenhouse gas contributing to global warming. , It is also a widely available, affordable, and benign source of carbon in the synthetic chemist’s toolbox . Thus, developing an effective method to use CO 2 has implications for environmental conservation and sustainable chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This is different from many other Ti-oxide clusters containing solely benzoate ligands, as the hydrophobic benzene rings often render them very soluble in nonpolar solvents and act as homogeneous catalysts in photocatalytic CO 2 /epoxide cycloaddition. [10][11][12]33 Therefore, the low solubilities of Ti 6 Mo 4 and Ti 4 Mo 4 could be attributed to the Mo�O terminal bonds. The catalytic reaction was conducted neatly at room temperature and 1 atm of CO 2 , with 1a serving as both the solvent and the reactant.…”
Section: Electronic Structuresmentioning
confidence: 99%
“…Titanium-oxide clusters (TOCs) are a category of molecular compounds characterized by discrete titania cores that are passivated with terminating ligand shells. These clusters serve as molecular counterparts to TiO 2 nanoparticles (NPs). , TOCs have garnered significant attention in recent years owing to their precisely engineered atomic architectures and considerable potential in the field of photocatalysis. A TOC may be effective in photocatalytic CO 2 /epoxide cycloadditions. Nevertheless, due to the comparable intrinsic band gap between TOCs and TiO 2 NPs, it is common for TOCs to demonstrate a relatively limited capacity for absorbing solar radiation.…”
Section: Introductionmentioning
confidence: 99%